A highly secured small-area low power decryption design - Chan, Jovince (Nanyang Technological University, 2021)
With the increasing rise of technological advancements causing the general public to store their sensitive data online, encryption is now a necessity to provide sufficient security to safeguard your sensitive data. Though Advanced Encryption Standard (AES) is known to be extremely secure such that it is impossible to break by the traditional hacking methods, it is however possible to break through the use of Side Channel Attacks (SCA). Although it is known that different designs for AES encryptions have different security levels, it is imperative to know what causes these designs to be stronger than others in terms of security. This research aims to discover these causes through the use of Correlation Power Analysis (CPA) on different AES-128 designs. The designs will be compared by comparing the number of traces required to fully obtain the cipher key of the encryption process.